Halo nevus with partial depigmentation. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
An 11-year-old boy presented from several years a 4 cm in size melanocytic dermal nevus on his back. His mother noticed from a few months a white halo on the medial surface of the nevus. The boy did not use sun screens and did not report traumas. His family history was negative for vitiligo and autoimmune diseases. On physical examination, there was a 1 millimeter in size white halo on the lower 2/3 of its medial surface (Fig. 1). On dermoscopy (Fig. 2), there was a cobblestone pattern, less evident and partially substituted by a whitish area level with the perinevic halo. The latter differed from the surrounding healthy skin, besides for its color, for the lack of the rhomboid outline of the skin. The final diagnosis was partial halo nevus and a wait and see policy was decided. Nine months later the partial halo did not change.